Quality of life of women with recurrent vulvar cancer treated with electrochemotherapy - Vivod, Gregor (Radiology and oncology (Ljubljana), 2025)
Background: The quality of life of patients undergoing oncologic treatment has become an important issue in recent years. Owing to potential mutilation following surgery for vulvar cancer, more conservative approaches have evolved with the integration of new local ablative therapies, such as electrochemotherapy. The aim of this study was to determine the quality of life of women with vulvar cancer recurrence treated with electrochemotherapy for nonpalliative purposes. Patients and methods: Eleven patients with vulvar cancer recurrence were treated with electrochemotherapy from July 2020 to December 2023. Patients completed different questionnaires: the EuroQol - 5 Dimension (EQ-5D), European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30), European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Vulva Cancer 34 (EORTC QLQ-VU34) and visual analog pain scale (VAS) before and one, three and six months after electrochemotherapy. As a control group, fifteen patients with vulvar cancer recurrence treated with wide local excision completed the EORTC QLQ-C30 and VAS questionnaires before surgery and three and six months after surgery. Results: No significant differences in EQ-5D scores were found between quality of life before electrochemotherapy and at each follow-up visit. A comparison of the EORTC QLQ-C30 scores between the electrochemotherapy and surgery groups showed a significant difference in physical functioning, fatigue, insomnia, and global health status three months after the procedure and in role, cognitive, social functioning and appetite loss six months after the procedure, all of which were in favor of the electrochemotherapy group. The EORTC QLQ-VU34 questionnaire showed improvements in urinary symptoms and symptoms related to scarring and mutilation of the external genitalia in the electrochemotherapy group. The VAS score did not differ significantly between the electrochemotherapy and surgical groups. Conclusions: The study showed that the quality of life after treatment with electrochemotherapy is better in some segments than after surgical treatment.
Keywords: bleomicin; bleomycin; electrochemotherapy; elektrokemoterapija; kvaliteta življenja; quality of life